PRODUKTIVITAS KEDELAI (Glycine max (L.) Merril var. Lokon) YANG DIPERLAKUKAN DENGAN PUPUK ORGANIK CAIR LENGKAP PADA DOSIS DAN WAKTU PEMUPUKAN YANG BERBEDA - Meirina, Tettrinica; Darmanti, Sri; Haryanti, Sri (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2009)
One ofthe way able to be conducted to improve productivity of soy is with treatment of organic fertilizer at different treatment time and dose. This research aim to to know influenceof liquid organic fertilization to soy crop productivity, knowing fertilization time and dose giving best result and also know interaction between fertilization time and dose. Researchconducted with Complete Random Device with factorial pattern . First factor of fertilization dose that is : D0 ( without treatment of manure), D1 ( 0,7 fertilizer ml / 1 water litre), D2 ( 1,4 fertilizer ml / 1 water litre) and D3 ( 2,1 fertilizer ml / 1 water litre). Second factor is time fertilization of T1 ( morning), T2 ( daytime) of T3 ( afternoon). Parameter perceived by hat isamounts of pod wet heavy of pod wet heavy of seed and dry heavy seed. Data to be analysed with ANOVA level of signification 95%, continued by test of Duncan level of signification 95%. Research result indicate that fertilization with liquid organic fertilizer complete can improve soy crop productivity, but difference of passed to dose is crop give result differ do not reality. Fertilization time at afternoon and morning cause compared to higher soy crop productivity in the day time. Fertilization in the afternoon differ reality to fertilization ofdaytime. Between fertilization dose and time there are interaction to high improvement of dry weight and crop of]soy seed.